Musculoskeletal disorders among preschool teachers: analyzing the relationships among relational demands, work meaning, and intention to leave the job - Daniela Converso; Sara Viotti; Ilaria Sottimano; Vincenza Cascio; Gloria Guidetti (BMC Musculoskeletal Disorders, 2018)
Abstract Background Based on the conservation of resource (COR) theory by Hobfoll, the aim of the present study was to test whether the relationships among relational demands, work meaning, and intention to leave vary as a function of the presence of musculoskeletal disorders (MSDs). Method The study was cross-sectional and non-randomized. Analyses were carried out on a dataset consisting of 429 preschool teachers, who filled out a self-report questionnaire. Of them, 238 reported a MSD diagnosis and 191 were free form MSDs. Results As expected, among those who reported MSDs, relational demands were significantly associated to intention to leave, and this relationship was mediated by work meaning; moreover, among those free from MSDs, no significant paths among the three variables were found. Conclusion In general, results showed that suffering from MSDs impairs workers’ ability to face to relational demands, thus activating a spiral that encompasses diminished work meaning and intention to leave. Practical implications of results will be discussed in the paper.